Data Format and Interface Design in Digital Identity Applications Using WSO2 - Yuki Indragiri Winata; Hermawaty Hermawaty; Muh Mujib (CCIT Journal, 2022)
This study aims to upgrade the application login system in STMIK "AMIKBANDUNG", from some problems that exist in a regular login system and with the development of an information system that requires STMIK "AMIKBANDUNG" to follow its development, not only various applications but companies are required to improve data security on the application login system. In the draft in this study proposes a single entry system (Single Sign On). By using this single login system, users only need to remember one user name and password to enter in various applications in the organization or company. In this study using open source WSO2 IS, and in the database system in WSO2 IS there is an embedded database system that is H2 database, in addition to H2 database, WSO2 IS provides a place for other database systems such as MYSQL. So in one identity provider this contains two database systems. And the results of the application of MYSQL database in this research allows WSO2 IS users to develop in various protocols in WSO2 IS, and use a simple and easy to understand interface format. So with this research, STMIK "AMIKBANDUNG" can upgrade the login system, with only one account can make it easier for students and staff to enter into one or more of the application services in STMIK "AMIKBANDUNG".